Kontrol On/Off Jarak Jauh Motor Induksi 3 Fasa Dengan Komunikasi Half-Duplex Menggunakan Zigbee - Febriko Fautama; Budhi Anto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Remote access for industrial operation of 3-phasess induction motor is so needed to reduce human errors it others benefits. Therefore, in this study remote access is design for the operation of 3-phases induction motor by also using Zigbee pro S1 and Arduino Uno as data transmission media. The control system in the 3-phases induction motor is a remote and an actuator unit. The remote control device is equipped with two Command Buttons for ON command and OFF command, and one Light Emitting Diode (LED) as an indikator of motor condition. The actuator unit is equipped with a motor driver circuit to operate the motor according to the received command. Feedback circuit reads the condition of motor then sent it back to the control device. From the entire results of testing, actuator unit can operate the motor in accordance with the